2021
DOI: 10.3390/su13147944
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Integrated Design Strategy for Blue-Green Architecture

Abstract: Blue-green architecture entails buildings that contribute to improving the urban climate through the synergetic combination of water management and vegetation. They are part of an urban blue-green infrastructure network that combines ecosystem services in a multifunctional way. Projects implemented in an interdisciplinary manner create synergies with regard to the combination of water-related and vegetation-related objectives. However, applicable design strategies for this approach are currently lacking in pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…A study by Broadbent [44] found that increasing irrigation on a grassland area in Lake Mason in Adelaide has a cooling effect of up to 1.75 • C at 13:00 and a small warming effect at night (<0.75 • C). The planning process in BGI projects require interdisciplinary cooperation, as it combines both greening and water aspects [45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Broadbent [44] found that increasing irrigation on a grassland area in Lake Mason in Adelaide has a cooling effect of up to 1.75 • C at 13:00 and a small warming effect at night (<0.75 • C). The planning process in BGI projects require interdisciplinary cooperation, as it combines both greening and water aspects [45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A wicked problem does not feature a comprehensive problem formulation and cannot be solved with one ultimate solution. Thus, wicked problems cannot be tackled by regular thinking and conventional scientific research approaches, but rather require counterintuitive thinking [23][24][25]. Therefore, the research questions are addressed through a research by design approach.…”
Section: Methodsmentioning
confidence: 99%
“…It is clear, however, that the phrase "blue-green infrastructure" is used in an urban environment, with a focus on stormwater control as a key component in developing a sustainable, multifunctional city [9]. Blue-green architecture [10] refers to a smaller scale use of these elements in building design. Greening buildings via the use of recycled water and other non-potable sources of water are the topic at hand.…”
Section: Introductionmentioning
confidence: 99%